Nitro-substituted polyamides: A new class of transparent and highly refractive materials. (May 2015) - Javadi, Ali; Shockravi, Abbas; Koohgard, Mehdi; Malek, Ali; Shourkaei, Fateme Ahmadi; Ando, Shinji
Graphical abstract: Highlights: Highly refractive and transparent polyamides (PAs) were developed. The refractive index of PA-5 was 1.7660, which is the highest value reported for PAs. The obtained PAs exhibited high heat resistance and excellent solubilities. The structure–property relationships of the PAs were studied. Abstract: High-refractive-index polyamides (PAs) were developed by introducing nitro groups, thiazole rings, and thioether linkages. The PAs were prepared by the polycondensation of a novel diamine monomer, 5, 5′-thiobis(2-amino-4-(3-nitrophenyl)thiazole) (DA), with various aromatic diacids. The bulky pendant nitrophenyl units, as well as the flexible thioether linkage in the diamine, endowed the resulting PAs with excellent solubilities in both amide-type polar aprotic solvents and less polar solvents. The obtained polymers exhibited high heat resistance, with 10% weight loss temperatures exceeding 472 °C under nitrogen and 427 °C in air atmosphere, while their glass transition temperatures were in the range 210–244 °C. The combination of the nitro substituents, thiazole units, and thioether linkages provided PAs with high refractive indices of up to 1.7660 at 632.8 nm, along with high transparency in the visible region and low birefringences (<0.0081). The structure–property relationships of these PAs due to the presence of nitro groups were also studied by comparing the results with the previously reported analogous polymers.